2014
DOI: 10.1007/s00284-014-0679-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Functional Characterization of the Hyaluronate Lyase HylB and the Beta-N-Acetylglucosaminidase HylZ in Streptococcus zooepidemicus

Abstract: Hyaluronic acid (hyaluronan) is a high molecular weight glycosaminoglycan composed of repeating disaccharides of glucuronic acid and N-acetylglucosamine. The molecular weight of hyaluronan is important for its rheological property, biological function, and application. However, genes important for regulation of hyaluronan production or molecular weight remain poorly understood. Here, we address the roles of two predicated hyaluronate lyase-encoding genes, hylB and hylZ in Streptococcus zooepidemicus. Semi-quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…ZnO is a material with excellent antibacterial activity in many drug-resistant pathogens, including S. aureus , Escherichia coli ( E. coli ) [ 36 ], and Candida albicans [ 37 ]. Compared to traditional metal bacteriostatic materials, when the size of ZnO is reduced to the nanometer range, ZnO QDs typically exhibit additional morphologies and significant antibacterial activity against various bacterial species, e.g., E. coli , S. aureus , and Salmonella pullorum , which have been explored by numerous researchers [ 18 , 38 , 39 , 40 ], prompting us to explore whether they also have inhibitory effects on drug-resistant S. agalactiae in our study. Our experimental results showed that the inhibition ability of ZnO QDs for S. agalactiae WJYT1 was concentration dependent.…”
Section: Discussionmentioning
confidence: 99%
“…ZnO is a material with excellent antibacterial activity in many drug-resistant pathogens, including S. aureus , Escherichia coli ( E. coli ) [ 36 ], and Candida albicans [ 37 ]. Compared to traditional metal bacteriostatic materials, when the size of ZnO is reduced to the nanometer range, ZnO QDs typically exhibit additional morphologies and significant antibacterial activity against various bacterial species, e.g., E. coli , S. aureus , and Salmonella pullorum , which have been explored by numerous researchers [ 18 , 38 , 39 , 40 ], prompting us to explore whether they also have inhibitory effects on drug-resistant S. agalactiae in our study. Our experimental results showed that the inhibition ability of ZnO QDs for S. agalactiae WJYT1 was concentration dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial HAases are recognized as good sources for HAase development with potential clinical applications. They are found in Bacillus [12,13], Streptococcus [14,15], Streptomyces [16], and other bacteria strains [17][18][19]. Most microbial HAases are hyaluronate lyases, which are convenient for operation and cost-effective for fermentation [17].…”
Section: Introductionmentioning
confidence: 99%